Comparative analysis of Chloris gayana and Urochloa ruziziensis and their intercropping potential in the Semi-arid Chaco (Semiárida, 2026)
Implanted pastures in the Semi-Arid Chaco are mainly composed of species with C4 carbon metabolism, whose growth occurs seasonally in the form of pulses, understood as patterns of growth and development associated with cyclical environmental fluctuations. In these systems, vegetation exhibits periods of accelerated growth under favorable conditions, mainly related to water availability and temperature, followed by a marked reduction or interruption of growth during unfavorable periods. Consequently, forage production decreases significantly in early summer and during autumn due to water deficit, low temperatures, frost events, and limited precipitation, resulting in a critical period of forage availability from late winter to early spring. Pastoral livestock systems in the region rely predominantly on monocultures of Megathyrsus maximus cv. Gatton Panic, which increases system vulnerability to environmental variability. In this context, diversification through the incorporation of species with different productive and management attributes could contribute to stabilizing forage supply and reducing production risks. This review systematizes available information on the morphology, edaphoclimatic requirements, management, productivity, and forage quality of Chloris gayana Kunth (Rhodes grass) and Urochloa ruziziensis (ruzigrass, Congo grass; sin. Brachiaria ruziziensis), with a comparative approach to analyze their potential for intercropping. Finally, the need to advance experimental trials to evaluate productivity, forage quality, and interspecific competition of these species at different proportions is highlighted.
Keywords: Forage mixtures; forage production; ecological niche; forage quality; species diversity; defoliation